2022
DOI: 10.1177/00207640221077580
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness in the presence of others: A mixed-method study of social networks of caregivers of patients with severe mental disorders

Abstract: Background: One in four families has at least one member with a mental disorder and families are the main caregivers in most patients in low and middle-income countries. Caregivers experience disruption in their routine lives, increased responsibilities, increased need for support, and changes in their network. The role of personal support networks in the health and burden of the caregivers is complex and depends on the context, cultural and socioeconomical variables. In this study, we aimed to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
4
7
0
Order By: Relevance
“…These family members were found to be experiencing, on average, at least moderate levels of loneliness in what is, to our knowledge, among the very first empirical studies of loneliness, social isolation, and stigma by association in a North American family member sample. The findings are consistent with recent research that found so-called ‘loneliness in the presence of others’ in family members who care for a relative with severe mental illness in Iran [ 6 ] and are also consistent with past research in Scandinavian family members [ 28 , 29 ]. Our findings also echo prior qualitative research that found family members of people with SMI experienced stigma by association and perceived themselves as lacking social support [ 7 , 30 ], particularly those who cohabited with their relatives [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These family members were found to be experiencing, on average, at least moderate levels of loneliness in what is, to our knowledge, among the very first empirical studies of loneliness, social isolation, and stigma by association in a North American family member sample. The findings are consistent with recent research that found so-called ‘loneliness in the presence of others’ in family members who care for a relative with severe mental illness in Iran [ 6 ] and are also consistent with past research in Scandinavian family members [ 28 , 29 ]. Our findings also echo prior qualitative research that found family members of people with SMI experienced stigma by association and perceived themselves as lacking social support [ 7 , 30 ], particularly those who cohabited with their relatives [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Family members who have a relative with SMI often assume demanding caregiving responsibilities that can become quite distressing [ 4 ] and place them at risk for burnout [ 5 ]. A recent mixed-methods study of family caregivers of individuals with SMI [ 6 ] poignantly depicted the extreme social isolation of these family members who were found to have exceedingly small social networks, an isolation which the authors ascribed to stigmatization. Specifically, family members reported the need to be “secretive about the (relative’s) mental illness… so they reduce their social interactions”.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with our expectations based on social role theory [42] and the gendered and familial nature of caregiving [35]. Focusing primarily on family had partly been indicated before [16,17]. Adding to this, the average quality of the network, in terms of contact frequency and closeness, did not change among inside caregivers.…”
Section: Network Changes Among Informal Carerssupporting
confidence: 89%
“…The composition of the network may also shift. Caregiving is mostly perceived as a feminine and family task [35], although previous findings on the relevance of family are mixed [16, 17]. Thus, caregivers may be more inclined to change their network in terms of adding more women and family members, in particular among inside caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…However, interventions that provide group‐based skills, support, and psychoeducation solely to loved ones of veterans with PTSD have not been tested. This modality is important given the isolation that loved ones of individuals with mental health conditions often report experiencing (Tabatabaee et al., 2022) and the potential benefits of receiving support and being able to ask questions about the diagnosis unencumbered by concerns about self‐censoring (Renshaw et al., 2020).…”
mentioning
confidence: 99%